2019
DOI: 10.1016/j.ebiom.2019.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Serial patient-derived orthotopic xenografting of adenoid cystic carcinomas recapitulates stable expression of phenotypic alterations and innervation

Abstract: Background Patient-derived xenograft (PDX) models have significantly enhanced cancer research, and often serve as a robust model. However, enhanced growth rate and altered pathological phenotype with serial passages have repeatedly been shown in adenoid cystic carcinoma (ACC) PDX tumors, which is a major concern. Methods We evaluated the fidelity of ACCs in their natural habitat by performing ACC orthotopic xenotransplantation (PDOX) in salivary glands. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…We then tried to generate PDX ACC model as Cornett et al has reported previously 25 . As shown in Figure 1, PDX ACC model have been successfully established from four of six ACC patients (YCU‐ACC‐10 could not be prepared for PDX procedure because of too small sample from the original tumor).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then tried to generate PDX ACC model as Cornett et al has reported previously 25 . As shown in Figure 1, PDX ACC model have been successfully established from four of six ACC patients (YCU‐ACC‐10 could not be prepared for PDX procedure because of too small sample from the original tumor).…”
Section: Resultsmentioning
confidence: 99%
“…We then tried to generate PDX ACC model as Cornett et al has reported previously. 25 As shown in Figure 1…”
Section: Generation Of Pdx Acc Modelmentioning
confidence: 90%
“…For example, Mitani et al reported that the level of MYB expression in identical histological subtypes of ACC is associated with a shorter survival time. Recently, xenografting and the first MYB‐NFIB‐positive cell line (UM‐HACC‐2A) have been established and represent interesting tools to explore novel therapeutic possibilities . Therapeutically, MYB‐targeted antisense oligodeoxynucleotides (G4460; INX‐3001; LR3001) have not been effective in clinical trials ; however, several lines of evidence suggest that MYB is a promising therapeutic target .…”
Section: Discussionmentioning
confidence: 99%
“…The research on adenoid cystic carcinoma (ACC), a rare relentless neoplasm arising in secretory glands, was limited by contaminated cell lines and traditional PDX, and a more accurate model system exhibiting important molecular features of this tumour was needed. To this end, Cornett and coworkers carried out the study published in this issue of EBioMedicine [8]. The group performed PDOX in salivary submandibular glands of immunodeficient mice and evaluated the fidelity of ACC during subsequent passages.…”
mentioning
confidence: 99%
“…Furthermore, genomic and molecular alterations unique to the original ACC were retained. Their data also demonstrates PDOX tumours as a sound model for drug testing [8].…”
mentioning
confidence: 99%